Understanding the influence of individual level factors of Anganwadi workers on service delivery under the Integrated Child Development Service scheme - Nair, Sajini B.; Hallad, Jyoti S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Anganwadi workers (AWW) of the Integrated Child Development Service (ICDS) Scheme are the agents of social change, mobilizing community support for better care and continuously addressing malnutrition among young children. The influence of individual background characteristics of AWWs on uptake of service delivery is rarely examined and forms the subject of inquiry. Methods: Data used pertain to information on 349 Anganwadi centres (AWCs) in 11 Indian states collected for a study on ICDS during 2021-22. Multivariate statistical methods were employed to derive the findings using SPSS version 20. Results: AWWs age, work experience, trainings received, residence in proximity to AWCs varies across districts under study. The mean number of services rendered of 11.9 out of the 14 types of services provided through AWCs indicate the overall competency of AWWs in rendering services. Sagar (MP), Solan (HP) and Dharwad (Karnataka) districts fall short of rendering complete services. Regression analysis indicate that presence of AWWs in their 50+ years in AWCs, greater experience of AWWs, increase in capacity building of AWWs and higher education levels strongly determine uptake of more services. Conclusions: ICT intervention entails digital literacy to implement programmes and web-based monitoring for better nutritional outcomes require better competency for AWWs. To cater to the changing needs perhaps a review of the guidelines on educational level of AWWs for recruitment and revamping the training programmes by focussing on skill-based training for AWWs to unlock the full potential of ICDS scheme workforce may be attempted.